Perancangan Aplikasi Messanger Dengan Menerapkan Caesar Shift Berbasis Secret Sharing - Bayu Syahputra (Journal of Computer System and Informatics (JoSYC), 2019)
The impact of chatting may not be realized at all. In addition to facilitating communication as a positive impact that humans get, there are also negative impacts that humans get as a result of using this chat. Confidentiality and security when exchanging data is very important in data communication, both for shared security purposes, and for individual privacy. the progress of the communication so many people who want to tap communication between one person and another that causes a lot of information or conversation is tapped without the knowledge of the owner of the information. There are several ways to secure data through an internet data channel, one of which is cryptography. Highly confidential data will be disguised in such a way that even if the data can be read it cannot be understood by unauthorized parties. Data to be sent and not yet encoded, then this plaintext will change to ciphertext. One of the algorithms that can secure the data discussed by the author is the Caesar Shift Algorithm.